Durability of carbon fibre reinforced polymer laminates used to reinforced concrete structures - Cabral-Fonseca, S. (2009)
Due to their excellent mechanical properties and easy application Carbon Fibre Reinforced Polymers (CFRP) are being successfully used to repair and renewing old and damaged civil engineering infrastructures. In particular, the method of strengthening concrete members with externally bonding of CFRP laminates has become increasingly popular. In fact, extensive research has shown that this technique can lead to a substantial improvement in the flexural and shear strength capacities of the member repaired. In such applications, materials involved will be exposed to outdoor environmental conditions, including humidity, water from rain, saline-water, ground water and high alkalinity solutions due to chemical composition of the concrete itself, as well as solar ultraviolet radiation. Thus, it is of great relevancy to study the durability of the materials involved, namely epoxy adhesives and CFRP laminates, as well as, the integrity of the entire system, when subjected to those environmental factors. This work is part of a much larger research study that is being made to predict the longterm behaviour of several commercial CFRP laminate/adhesive systems used in the rehabilitation of concrete structures. In the whole project it is recognized that the durability of these solutions depends, not only on the durability of the composite materials but also on the performance of the systems used to bond them to the concrete. The present document provides details about the part of the investigation concerning the durability of CFRP laminates. This paper describes the study carried out to investigate the environmental and accelerated ageing effects on three types of commercially available CFRP laminates. The changes in CFRP laminates properties after exposure up to 18 months under different environmental conditions - immersion in demineralised water, saline and alkaline solutions at room temperature, 40 ºC and 60 ºC, as well as under constant humidity condensation atmosphere at 40 ºC – are reported and discussed. The results of tests performed in accelerated weathering chambers – with ultraviolet radiation – are also included. Results obtained offer valuable information about the progression of material degradation under different ageing conditions (some of them accelerated), which can be used, not only to characterize the behaviour of CFRP laminates, but also for a better understanding of the degradation mechanisms involved, which is a base for the design of service life-prediction models.